Differences in regional sweating responses during exercise between athletes trained on land and in water - Kondo, N.; Nishiyasu, T.; Nishiyasu, M.; Ikegami, H. (European Journal of Applied Physiology, 1996)
We investigated whether there are any differences in regional sweating responses during exercise between athletes trained on land and in water. We measured the local sweating rates on the left forearm (mswf) and the left scapula (msws), body temperatures (mean skin temperature, and rectal temperature Tre) in eight athletes trained on land (five soccer players, one distance runner and two baseball players, L group) and seven athletes trained in water (seven swimmers, W group) during cycle ergometer exercise at 50% maximal oxygen uptake for 40 min. The heart rate and oxygen uptake in the two groups during exercise showed nearly the same pattern of change. The Tre at the end of the exercise were 38.13 (SEM 0.19) degrees C in the L group and 38.26 (SEM 0.34) degrees C in the W group. Although the mswf in the two groups were similar, msws were significantly higher in L than in W at 30, 35 and 40 min of exercise. The msws at any given mean body temperature tended to be greater in L than in W. These results showed that a difference in regional sweating rate during exercise between the athletes trained on land and in water was present on the scapula.